PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Endri, Endri (Jurnal Keuangan dan Perbankan, 2012)
The objective of this study was to examines the relationship among ownership structure, the proportion ofindependent commissioner board and syariah banking performance. This study employed a stepwise regressionmethod to test the hypothesis that ownership structure and the proportion of independent commissionerboard affected finance performance of syariah bankingpositively. The result of analysis showed that there wasno significant relationship between managerial and domestic institutional ownership and bank syariah performance.But there was a significant positive relationship between foreign institution ownership and return onasset, and also between the percentage of independent board director and return on equity.